Silhouette of Beethoven by Lindler - Lindler, Enid Elliott (artist):::Creator:::::::::::: (Torquay; United Kingdom; Pennyfarthing Galleries, 2022)
Silhouette of Beethoven published by the Pennyfarthing Galleries. Companion to g1f007.